BIOKONVERSI KARBONDIOKSIDA UNTUK BAHAN BAKU INDUSTRI - Untung Suwahyono (Jurnal Teknologi Lingkungan, 2008)
From the stand point of carbon dioxide cycle on global warming, the conversion of CO2 into various useful carbonic material compound is one solution. Using natural energy sources such as LNG and cole may contribute to CO2 removal in the atmosphere. As one of feasible measure though CO2 is final oxidized product of carbon containing reaction have been proposed and investigate. Biological proces have to developed, CO2 was efectivly converted to methan, acetat, and raw material for plastic degradable.